Analysis of occupant crash protection in designing lightweight automotive side member - Intan Salwani, Mohd Salleh, Dr.; Aidy, Ali, Assoc. Prof. Dr.; Barkawi, Sahari, Prof. Dr. Ir.; Nuraini, Abdul Aziz; Faieza, Abdul Aziz, Dr.; Tuan Hafandi, Tuan Ismail; J. Mai Nursherida; Nabilah, Mohd Safar; Shahril, Mohamad; Norhidayah, Muhamed (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia